1952
DOI: 10.1001/jama.1952.03680050012004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Independent Paroxysmal Tachycardias

Abstract: tory gastroenterostomy. The last mentioned would seem most plausible while the former two are merely conjectural. Gradman and his colleagues feel that gastro¬ enterostomy is the simplest and safest procedure, pro¬ viding that the gastric wall at the anastomotic site is nor¬ mal. We agree with this completely. In our two cases posterior gastrojejunostomy yielded excellent results. If a direct anastomosis is not feasible, then the procedure of choice is a subtotal gastric resection. SUMMARY Two cases of stenotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1954
1954
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The ventricular rate speeds up before the pause after R5, the shortest interval precedes the pause and the first cycle following the pause is greater (0.80 second) than that preceding it (0.72 second), and the pause itself is shorter than the sum of any 2 consecutive short cycles. This arrangement is typical of the Wenckebach phe- 14 shows the effect of an atrial extrasystole during interference dissociation. The fifth P wave represents an extrasystole that is conducted to the ventricle.…”
Section: Interference Dissociation Between An S-a Andmentioning
confidence: 76%
“…The ventricular rate speeds up before the pause after R5, the shortest interval precedes the pause and the first cycle following the pause is greater (0.80 second) than that preceding it (0.72 second), and the pause itself is shorter than the sum of any 2 consecutive short cycles. This arrangement is typical of the Wenckebach phe- 14 shows the effect of an atrial extrasystole during interference dissociation. The fifth P wave represents an extrasystole that is conducted to the ventricle.…”
Section: Interference Dissociation Between An S-a Andmentioning
confidence: 76%
“…The terms, "double tachycardia" or "simultaneous tachycardias" are defined as the simultaneous occurrence of independent atrial and ventricular (or junctional) tachycardia (7,8). This type of tachycardia has been observed mainly in digitalis intoxication, generally in patients with poor left ventricular function (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported intra atrial dissociation with simultaneous tachycardias as "atrial double tachycardia" (13). In these reports, double tachycardia was diagnosed by the recording of two dissociated and independent electrograms of each tachycardia (7)(8)(9)(10). If the interval of one potential was variable, various types of the second degree block between the two electrograms should be excluded.…”
Section: Discussionmentioning
confidence: 99%